Lactylation, an emerging hallmark of metabolic reprogramming: Current progress and open challenges - Liu, Xuelian; Zhang, Yu; Li, Wei; Zhou, Xin (Frontiers in Cell and Developmental Biology, 2022)
Lactate, the end product of glycolysis, efficiently functions as the carbon source, signaling molecules and immune regulators. Lactylation, being regulated by lactate, has recently been confirmed as a novel contributor to epigenetic landscape, not only opening a new era for in-depth exploration of lactate metabolism but also offering key breakpoints for further functional and mechanistic research. Several studies have identified the pivotal role of protein lactylation in cell fate determination, embryonic development, inflammation, cancer and neuropsychiatric disorders. This review summarized recent advances with respect to the discovery, the derivation, the multi-organism landscape, and the diverse functions of lactylation. Further, we thoroughly discussed the discrepancies and limitations in available studies, providing optimal perspectives for future research.